General practice audit of asthma in childhood. Issue 6452 (27th October 1984) - Levy, M; Bell, L
Abstract : It has been suggested that asthma is underdiagnosed in children. We studied the records of 52 children with asthma in our group practice. Although asthma had been positively diagnosed in roughly 10% of the children aged 18 months to 11 years, to make the diagnosis required an average of 16 to 20 consultations for respiratory problems. According to the symptoms recorded before the diagnosis was made, only three quarters of the children had presented with wheeze and roughly a third had had difficulty in sleeping. We think that the doctor's time would be better spent teaching patients about their asthma than by repeatedly treating non-existent respiratory infection.